Left ventricular restrictive physiology in kids with atrial septal defects: Something unexpected! - Alessia Faccini; Matteo Casenghi; Mario Carminati; Gianfranco Butera (Wolters Kluwer Medknow Publications, 2021)
Atrial septal defect (ASD) associated with left ventricular (LV) diastolic dysfunction (DD) is rare in children. DD is common in elderly patients undergoing ASD closure. Restrictive physiology among children undergoing percutaneous ASD closure is something unexpected that has not been described before in the literature. Hence, we report on a case of a child referred to our center for ASD closure in which an LV DD has been unmasked with a balloon occlusion test and has been managed with pharmacological preconditioning and subsequent ASD closure with good outcome. Albeit rare, LV DD can occur on children undergoing ASD closure.